Integrative Literature Review Analysis of Indigenous Chicken Micro-Farming Value Chain: Preliminary Studies towards Transforming Indigenous Chicken Micro-Farming - Abbasi, I.A. (Association for Computing Machinery, 2021)
Indigenous chicken livestock micro-farming is a source of food and livelihood for poor household living in rural areas across the globe. Indigenous chicken micro-farming has a potential to be social sustainable business due to ability to perform well under triple bottom line parameter. Despite the potential to be a social sustainable business, indigenous chicken micro-farming is underdeveloped and unable to generate stable income for rural poor. Therefore, this study aims to identify key actors in indigenous chicken production and the role of each actor in the supply chain. The study further analyzes the value chain of indigenous chicken to categorize constraints experienced by each actor in the rural poultry. Integrative Literature Review (ILR) method is used to analyze the value chain of indigenous poultry to identify constraints. The results of analyses have shown that indigenous chicken industry lack well established optimal supply chain and there is a need to integrate all actors and channels involved in indigenous chicken business. Â© 2021 ACM. Copyright held by the owner/author(s). Publication rights licensed to ACM.